Clinical versus fixed warfarin dosing and the impact on quality of anticoagulation (The ClinFix trial) - Amr M. Fahmi; Ahmed El Bardissy; Mohamed Omar Saad; Mohamed Nabil Elshafei; Loulia Bader; Ahmed Mahfouz; Mohamed Kasem; Osama Abdelsamad; Abdelnasser Elzouki; Christina L. Aquilante; Fatima Mraiche; Ezeldin Soaly; et al. (Wiley, 2024)
Abstract Different dosing strategies exist to initiate warfarin, most commonly fixed warfarin dosing (FWD), clinical warfarin dosing (CWD), and genetic‐guided warfarin dosing (GWD). Landmark trials have shown GWD to be superior when compared to FWD in the EU‐PACT trial or CWD in the GIFT trial. COAG trial did not show differences between GWD and CWD. We aim to compare the anticoagulation quality outcomes of CWD and FWD. This is a prospective cohort study with a retrospective comparator. Recruited subjects in the CWD (prospective) arm were initiated on warfarin according to the clinical dosing component of the algorithm published in www.warfarindosing.org. The primary efficacy outcome was the percentage time in the therapeutic range (PTTR) from day 3 to 6 till day 28 to 35. The study enrolled 122 and 123 patients in the CWD and FWD, respectively. The PTTR did not differ statistically between CWD and FWD (62.2 ± 26.2% vs. 58 ± 25.4%, p = 0.2). There was also no difference between both arms in the percentage of visits with extreme subtherapeutic international normalized ratio (INR) (<1.5; 15 ± 18.3% vs. 16.8 ± 19.1%, p = 0.44) or extreme supratherapeutic INR (>4; 7.7 ± 14.7% vs. 7.5 ± 12.4%, p = 0.92). We conclude that CWD did not improve the anticoagulation quality parameters compared to the FWD method.